Writing abstracts in higher education: types of discourse - Teixeira, Carla (2019)
Courses on academic writing have become more frequent in higher education to face the challenges of communication on a specific social domain with which students have little or no previous contact. This study analyses a corpus of abstracts produced by undergraduates attending a course on Portuguese Academic Writing in a higher education institution (Cardoso, Sebastião & Teixeira 2018). We adopt the Socio-Discursive Interactionism (SDI) framework, which considers that there is an intrinsic dynamics to each social activity and each text genres has relevant linguistics markers (Bronckart 2008; Dolz, Noverraz, Schneuwly 2001). Special highlight will be given to types of discourse as packages of linguistics units based on mind operations: temporal disjunction or conjunction and enunciative implication or autonomy. Thus it is our aim to demonstrate how socio-discursive analysis tools describe student’s performance on Portuguese Academic Writing. According to data, students progressively acquire some skills more easily than others, especially those related to macrostructure as text plan; however, acquiring the specificities of theoretical discourse, a type of discourse featured by the temporal conjunction in the present and the enunciative autonomy, demands a special effort.